2007
DOI: 10.1080/10963758.2007.10696895
|View full text |Cite
|
Sign up to set email alerts
|

Competencies and Opportunities for Entry Level Golf and Club Management Careers: Perceptions from the Industry

Abstract: Employee recruitment in the golf and club management industry is a significant and challenging issue. This study examined the expected competencies and career opportunities for entry level management positions. Evidence revealed a broad spectrum of competencies, including food and beverage, leadership and strategic management, and financial accounting. Recruitment strategies to reduce vacancies and attract qualified applicants were generated, including credentialing, internships, and opportunities for current … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 28 publications
(11 citation statements)
references
References 19 publications
1
10
0
Order By: Relevance
“…Fjelstul (2007) examined competencies for entry-level club managers and "grooming and image" ranked third in the domain of knowledge skills. Targeting the hotel industry, Tesone and Ricci (2006) revealed that knowledge of "grooming and professional image" standards was ranked as the number one knowledge skill.…”
Section: Neatness and Groomingmentioning
confidence: 99%
“…Fjelstul (2007) examined competencies for entry-level club managers and "grooming and image" ranked third in the domain of knowledge skills. Targeting the hotel industry, Tesone and Ricci (2006) revealed that knowledge of "grooming and professional image" standards was ranked as the number one knowledge skill.…”
Section: Neatness and Groomingmentioning
confidence: 99%
“…In addition to looking at work experience in a generic sense, important competencies for entry-level managers include handling guest problems, following guest service standards, and operating under pressure; such skills may develop only or primarily with work experience (Christou, 2002;Fjelstul, 2007;Kay and Russette, 2000;Tas, 1988;Tesone and Ricci, 2005;Wilson et al, 2000). Using a framework of a human capital model, Mincer (1974) demonstrated that work experience is critical in interpreting variations in career earnings.…”
Section: Work Experiencementioning
confidence: 97%
“…Interpersonal skills-sometimes referred to generically as communication skills-have been ranked among the five most important skills for entry-level managers by hospitality industry leaders (ChungHerrera et al, 2003;Fjelstul, 2007;Kay and Russette, 2000;Mayo and Thomas-Haysbert, 2005;Tesone and Ricci, 2005).…”
Section: Interpersonal Skillsmentioning
confidence: 98%
See 2 more Smart Citations